STRESS ASSESSMENT OF BACTICIDE ON THE WATER BUG Diplonychus rusticus (HEMIPTERA: BELOSTOMATIDAE) - VASSOU, MIRIAM CECILIA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Use of pesticides such as bacticide in controlling mosquitoes at their breeding sites may have a negative effect on non-target species including the promising biological agents such as the belostomatid water bugs. In view of these considerations, the present investigation focuses on the extent of survival, tolerance and behaviour of the water bug Diplonychus rusticus in the fresh water medium tested with bacticide. The outcome of the results is discussed in the light of environmental stress on its population dynamics.